A study on homeownership constraints among millenials in Bandaraya Melaka / Mirrah Husna Mohd Razlin - Mohd Razlin, Mirrah Husna (2023)
In comparison to earlier generations, millennials are having more difficulty becoming homeowners due to shifting socioeconomic conditions and growing housing costs. This research aims to find out the homeownership constraints among the millennial generation from demographic and others related factor. To achieve the aims of this research, two (2) objective was developed which are objective one: to identify the factors that influence homeownership constraints among millennials, objective two: To rank the most important factor influence the homeownership constraints among millennials. When referring to the constraints, barriers, and delays in homeownership, a few factors identify in this paper, such as liability, location, financial, neighborhood, and developer. The survey was distributed to 163 millennial respondents of various statuses.